A history of water engineering and management in Yemen : material remains and textual foundations - Hehmeyer, Ingrid (Brill, 2019)
"In A History of Water Engineering and Management in Yemen, Ingrid Hehmeyer describes the three-way relationship between water, land, and humans from ancient to medieval and premodern times. As illustrated in case studies from four sites, individual ecosystems necessitated different engineering and management approaches in order to make good use of the scarce water resources for both irrigated agriculture and domestic consumption. Material remains and written sources provide the evidence for a comprehensive examination of continuity and change; technical and managerial struggles, failures, and successes; the question of technology transfer; the impact of the religion of Islam on water use and allocation; and people's reactions in times of severe crisis."--Back cover
Keywords: Water-supply engineering -- Yemen (Republic) -- History.; Water-supply -- Yemen (Republic) -- History.; Eau -- Approvisionnement -- Technique -- Yémen -- Histoire.; Eau -- Approvisionnement -- Yémen -- Histoire.; BUSINESS & ECONOMICS -- Infrastructure.; SOCIAL SCIENCE -- General.; Water-supply; Water-supply engineering; Yemen (Republic); History